2009
DOI: 10.1590/s1516-635x2009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternally-derived antibodies on the performance and immunity of broilers induced by in ovo or post-hatching immunizations with a live vaccine against infectious bursal disease

Abstract: The interference of low or high maternal antibodies titers on the attenuated infectious bursal disease (IBD) virus (IBDV) vaccine infection and its effects on the performance of broilers vaccinated at the 18th day of incubation (in ovo), at one day of age (subcutaneously-SC), or at 15 days of age (drinking water-DW) were investigated. After a series of three live vaccinations, breeders were given or not an IBD oil emulsion vaccine (IBD-OEV) prior to sexual maturity. At day 18 of incubation (in ovo), a commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Immunosuppression is directly related to the integrity of the bursal tissue. Studies reporting bursal tissue lesions caused IBD vaccine viruses showed that they may induce similar or even more severe lesions than field viruses (Michell, 2009). The bursal lesions found in the present study are consistent with those reported in poultry with immunosuppressive diseases, including lymphoid depletion and necrosis, intermolecular inflammatory infiltration, edema, and hyperemia.…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of supporting
confidence: 90%
“…Immunosuppression is directly related to the integrity of the bursal tissue. Studies reporting bursal tissue lesions caused IBD vaccine viruses showed that they may induce similar or even more severe lesions than field viruses (Michell, 2009). The bursal lesions found in the present study are consistent with those reported in poultry with immunosuppressive diseases, including lymphoid depletion and necrosis, intermolecular inflammatory infiltration, edema, and hyperemia.…”
Section: Effect Of Embryo Thermal Stimulation On the Serum Levels Of supporting
confidence: 90%
“…Thus, the effect of vaccine strain was detected significantly only at 28 days of age in field observation 1 where there was a higher level of maternal antibodies on the first day ( Table 2). The neutralizing effect of passive antibodies on the moment of "vaccine uptake" is well known and widely discussed in literature about conventional vaccines (MICHELL et al, 2009). The results of this study show that this dynamics occurs in a similar way when vaccines with immune complex technology are used, delaying the detection of the effect of the vaccine strain on the bursal parenchyma of birds that have higher maternal antibodies.…”
Section: Discussionmentioning
confidence: 58%
“…The study revealed that 73.6% maternal antibody transfer rate [23]. Researchers confirmed that the level of MDA of chicks was below the level of protection between 15-20 days [24] and 15 days [25] and 4-7 days [26] after hatching. However, the use of different types of vaccine and vaccination schedules affects the protection of MDA [24].…”
Section: Discussionmentioning
confidence: 94%